Double and quadruple deletion mutant of EHV-1 is highly attenuated and induces optimal immune response. Issue 5 (27th January 2023) - Balena, Venkataramireddy; Pradhan, Stephanie S.; Bera, B.C.; Anand, Taruna; Sansanwal, Rekha; Khetmalis, Rhushikesh; Madhwal, Aashwina; Bernela, Manju; Supriya, K.; Pavulraj, S.; Tripathi, B.N.; Virmani, Nitin
Abstract: Equid alphaherpesvirus 1 (EHV-1) infection causes significant health problems in equines. The EHV-1 infection leads to abortion storm in mares, respiratory disease and myeloencephalopathy. Despite the wide use of vaccines, the outbreaks of EHV-1 infections keep occurring globally, suggesting the need for the development of improved vaccines. Gene deletion attenuated mutant viruses could be a good candidate for the development of modified live vaccines. Here, we report the generation of mutant EHV-1 by deleting virulence (glycoprotein E & internal repeat 6; IR6) and immune evasive (pUL43 & pUL56) associated genes either individually or in combinations; and comprehensive evaluation of mutants through in vitro characterization followed by in vivo study in murine model to adjudge the attenuation of the virus and immune responses generated by mutants vis-à-vis wild type (wt) virus. The EHV-1 mutants with deletion of IR6 and gE genes (vToH-DMV) and four genes (i.e., gE, IR6, pUL43 and pUL56) (vToH-QMV) revealed a significant reduction in plaque size with minimal loss in replication efficiency in comparison to the wt virus. Further, in vivo studies showed virus attenuation adjudged through significant reduction in clinical signs, weight loss, gross and histopathological lesions in comparison to wt virus also revealed improved immune responses estimated through serum neutralization and flow cytometric analysis of CD4 + and CD8 + cell populations. Thus it can be concluded that EHV-1 mutants viz. vToH-DMV and vToH-QMV (novel combination) are promising vaccine candidates and qualify to be studied for adjudging the protective efficacy with wt virus challenge.